Establishment of a system for regeneration and transfor-mation in peanut (Arachis hypogaea L.) using somatic embryo - Thu Nga, Nguyen Thi; Binh, Le Tran (Academia Journal of Biology, 2012)
Currently, plant cell biotechnology has providing advanced method, especially systems for development of transgenic plants via Agrobacterium tumefaciens, to develop plant varieties with improved resistance to diseases and pests and better tolerance to abiotic stresses. In the case of peanut (Arachis hypogaea L.) methods for in vitro plant regeneration and gene transfer using callus tissue have been reported. In this study, peanut cultivar L12 was used for development of an effective system generation for somatic embryos, multiple shoots, rooting of regenerated plantlets and then for testing the efficiency of transformation using gus gene and somatic embyos. Our results showed that the MS medium supplemented with 20 mg/l of 2,4 D proved to be most suitable for somatic embryo induction (14.9 embryos/1 embryos); and the MS medium supplemented with 2 mg/l of BAP was most effective in multiple shoot regeneration; rooting of regerated shoots was succesfull in MS medium containing 0.3 mg/l of IBA; The use of the developed generation system for transfer of gus gene via Agrobacterium - mediated method has resulted gus positive transformed plants. Thus, the system could be asseful for the transfer of valuable genes in peanut.